Self-knowledge and behavior: tips of philosophes and people’s wisdom - Rubanau, Anatoly V. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
The philosophical tradition of understanding the phenomenon of self-knowledge and its role in human life is presented. The essence of self-knowledge, its basic methods, place in the formation of self-esteem and the meaning of life are revealed. Concrete methods of purposeful mastery of a person’s own consciousness, emotional state and behavior are shown. The place of the self-knowledge in terms of it influence on behavior reflected in proverbs and sayings has been duscussed.
Keywords: self-knowledge; self-esteem; meaning of life; consciousness; emotional condition; behavior; folk wisdom